(untitled) (Research, Society and Development, 2022)
The present study aims to address the epidemiological profile of dengue cases in the municipality of Palmas – Tocantins from January 2015 to September 2020. This is a retrospective, cross-sectional and descriptive study. All the SINAN notification forms, from individuals of all age groups who have been diagnosed with dengue in the municipality between the referred period will be part of this study. Regarding dengue notifications in the SINAN system, in Palmas – Tocantins, in the period from 2015 to 2020, there was a total number of 14.533 confirmed cases of dengue, with 2019 being the year with the highest number of registrations, with 1.743 confirmed cases. In the study, there was a significant prevalence in the notifications of dengue cases in urban areas rather than peri-urban and rural areas. There was also a slight prevalence of registries in females, 51,7% in comparison to the male gender. It was also observed a sharp drop in the numbers of suspected and confirmed cases of dengue in 2020 compared to the other years. It was concluded that there is a current need to improve the knowledge of health professionals regarding an adequate registration of the parameters of the SINAN notification form, since dengue continue to be the main arbovirus disease to affect endemic cities. In addition, the absence of data or underreporting impairs the gathering of realistic information, compromising the approach and development of public policies to fight dengue.